Petrography and Geochemistry of the Early-Middle Devonian sandstones of the Padeha Formation in the North of Kerman, SE Iran. Implications for provenance - Zand-Moghadam, Hamed (2013)
Fil: Fil: Zand-Moghadam, Hamed. Department of Geology, Faculty of Science, Ferdowsi University of Mashhad, Iran